25th annual congress of the European College of Sport Science, 28th - 30th October 2020, Book of abstracts (European College of Sport Science, 2020)
The COVID-19 virus is causing much human suffering and economic hardship on a global scale. The ECSS Executive and Scientific Boards have done all that is possible to assess the full picture of how the virus has impacted, and can impact the College moving forward amidst the current chaos, uncertainty and instability. After careful consideration, and very detailed discussions, we have decided to cancel the ECSS Sevilla 2020 Congress and to organise the 25th ECSS Anniversary Congress, 28-30 October 2020, which will be a virtual congress. The scientific programme offers a broad interdisciplinary spectrum of current research in sport science. The highlights of this congress will be the live streams of three plenary sessions, more than 25 invited sessions, and the Young Investigators Award (YIA) presentations. In addition you will be able to access and view a huge amount of video streamed oral, traditional poster and e-poster presentations. The entire 25th ECSS Anniversary Congress programme will be made available for you, via your personal ECSS account, until the end of December 2020. This virtual congress will be a new experience for all of us. We are confident that with resilience and a spirit stronger than ever before, it will be a fantastic experience for all involved. We hope that you enjoy the 25th ECSS Anniversary Congress and we are already looking forward to welcoming you in person at the new ECSS Sevilla Congress in 2021! Yours in sport science, Erich Müller, ECSS President Flemming Dela, Chair ECSS Scientific Board Elias Tsolakidis, ECSS Technical Director